Unsociability and social adjustment in Chinese preschool migrant children: the moderating role of receptive vocabulary - Zhu, Jingjing; Xiang, Shuhui; Yin, Xiaoqi; Li, Yan (Frontiers in Psychology, 2024)
Peer relationships play an indispensable role in the social, emotional, and cognitive development of children. However, children exhibiting social withdrawal, such as unsociability, may face challenges in social adjustment. In collectivistic cultures like China, unsociability may be perceived negatively, aligning poorly with collective norms. The objective of the present investigation was to examine the associations between unsociability, receptive vocabulary, and indicators of social adjustment in a cohort of young migrant children residing in urban regions of mainland China. The study mainly aimed to investigate the potential moderating influence of receptive language on these associations. The study involved 148 young children (82 boys, 66 girls, Mage = 62.32 months, SD = 6.76) enrolled in preschools or kindergartens in Shanghai, People’s Republic of China. Multiple sources of assessment were utilized, encompassing evaluations from mothers (about child unsociability), teacher (assessing social adjustment), and standardized tests (measuring receptive vocabulary). The results indicated that the relations between unsociability and peer exclusion were more positive among children with lower levels of receptive vocabulary but not significant for children with higher levels of receptive vocabulary. Similarly, the relations between unsociability and peer exclusion were more negative among children with lower levels of receptive vocabulary but not significant for children with higher levels of receptive vocabulary. Thus, this study informs us about how receptive vocabulary is jointly associated with unsociable children’s development. As well, the findings highlight the importance of considering the meaning and implication of unsociability in Chinese culture.